166k views
5 votes
Find the y-intercept of the function y = -3(x+2)(x-1)(x+3)

1 Answer

3 votes

The y-intercept of a function happens when the function "cuts" the y-axis.

This can be calculated as the value of the function f(x) when x=0.

Then, if we replace x by 0, we get the y-intercept:


\begin{gathered} f(x)=-3\mleft(x+2\mright)\mleft(x-1\mright)\mleft(x+3\mright) \\ f(0)=-3(0+2)(0-1)(0+3) \\ f(0)=-3\cdot2\cdot(-1)\cdot3 \\ f(0)=18 \end{gathered}

The y-intercept for this function is f(0)=18.

User Mlapaglia
by
5.5k points